A invenção da juventude transviada no Brasil (1950-1970) - Santos, Lidia Noemia Silva dos (2013)
This thesis is a wayward youth story ( rebels without a cause ), a contingent of young, mostly male and from the wealthier layer of society, who assumed in an esthetic and behavioral plan, a cultural identity considered transgressive and delinquent, between 1950 s and 1970 s. From the analysis of journalistic and academic studies sought to analyze how emerged that youth culture in Brazil and how it was meant for intellectuals who sought to explain it. Moreover, this work intention is to recover the practice and representations of wayward young in a context of culture transnationalization which meant, among other things, growth of urban living, expansion of media consumption and approximation with American culture